Fermented straw as livestock feed - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
Wheat and rice straws often form the main roughage in the diet of livestock, but they are poor in protein and digestible nutrients. Now researchers at two Indian universities have developed a technique for producing fermented straw.The straw is...